(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In today’s crowded market, companies and businesses are looking for different ways to introduce their products to consumers. One of them is by addressing social media influencers for advertisement. This paper examines how social media vlogs influence consumer behavior, including their brand perceptions and purchase decisions. The study is based on the analysis of contemporary academic literature from above 2015 years and the author’s personal observations. The article also highlights the role of vloggers as opinion leaders, the importance of content authenticity, and the emotional involvement of the audience. The key mechanisms through which influencers build trust and influence consumer preferences are discussed. It concludes with recommendations for marketers and directions for future research.